2016
DOI: 10.1253/circj.cj-16-0030
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid as a Risk Factor for Chronic Kidney Disease in a Japanese Community – The Hisayama Study –

Abstract: Background: Growing evidence suggests that high serum uric acid (SUA) levels are causally related to increased risk of chronic kidney disease (CKD). However, few studies have investigated the influence of elevated SUA levels on the incidence of kidney dysfunction and albuminuria separately in community-based populations. Methods and Results:A total of 2,059 community-dwelling Japanese subjects aged ≥40 years without CKD were followed for 5 years. CKD was defined as kidney dysfunction (estimated glomerular filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 30 publications
5
38
0
Order By: Relevance
“…Comprehensive surveys of cognitive impairment in the elderly of this town have been conducted since 1985 11. In 2002 and 2003, 1760 residents aged 60 and older (participation rate 83.4%) underwent a screening examination for the present study 12. After excluding 122 subjects who already had dementia at baseline, 31 for whom no urine sample was obtained, 1 for whom no blood sample was obtained, and 44 for whom no educational information was obtained, the remaining 1562 subjects (672 men, 890 women) were enrolled in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensive surveys of cognitive impairment in the elderly of this town have been conducted since 1985 11. In 2002 and 2003, 1760 residents aged 60 and older (participation rate 83.4%) underwent a screening examination for the present study 12. After excluding 122 subjects who already had dementia at baseline, 31 for whom no urine sample was obtained, 1 for whom no blood sample was obtained, and 44 for whom no educational information was obtained, the remaining 1562 subjects (672 men, 890 women) were enrolled in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous epidemiological studies have reported that elevated serum uric acid level was associated with an increased risk of CKD [11][12][13][14][15][16], but moderate alcohol consumption was associated with decreased risk of CKD [17][18][19][20]. The comparative importance and joint relationship of elevated serum uric acid and alcohol consumption to the risk of CKD has not been confirmed well.…”
Section: Introductionmentioning
confidence: 94%
“…The comparative importance and joint relationship of elevated serum uric acid and alcohol consumption to the risk of CKD has not been confirmed well. Only 4 prospective studies of healthy middle-aged adults are available on relating serum uric acid to the risk of incident CKD after adjustment for alcohol consumption [13][14][15][16]. Of them, 3 studies used alcohol consumption levels as a dichotomous variable and did not describe its definition clearly [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, on the basis of the well-known relationship between serum uric acid (SUA) level and renal function deterioration [4,5], hyperuricemia is an independent risk factor [6] that impairs each of renal functions, i.e. glomerular filtration rate and albuminuria.…”
Section: Introductionmentioning
confidence: 99%